Verreaux, Vi (audio interview #1 of 1) - Verreaux, Vi (b. 5/27/1935 - d. 1999); Schulheis, Cynthia, interviewer
INTERVIEW DESCRIPTION - A single relatively short interview was conducted with Vi Verreaux as a project for a directed studies in oral history. Despite a heart problem that restricted her activities, the narrator was lively and had a very good memory. Unfortunately, plans for subsequent interviews were never realized and, as a result, the documentation on the founding and early days of T.H.E. Clinic for Women is thin. [Note: the acronym stands for "To Help Everyone."] 10/28/1992